A COMPARATIVE MORPHOLOGICAL STUDY OF THE KOS-NISYROS-TILOS VOLCANOSEDIMENTARY BASINS - Nomikou, P.; Papanikolaou, D. (Bulletin of the Geological Society of Greece, 2010)
A swath bathymetric map of Kos-Nisyros-Tilos Volcanic field was created with 50m grid interval, with 10 m isobaths at a scale 1:100.000 using SEABEAM 1180 (180 kHz) multibeam system for depths <500m and SEABEAM 2120 (20 kHz) multibeam system for depths >500m. Five basins have been distinguished in the circum-volcanic area of Nisyros: 1)Eastern Kos basin, the larger and deeper one, with an average sea-bottom depth of 630m. Submarine canyons within the basin occur along the southern coastline of Kos cutting the isobaths from 150 up to 400m depth. A shallow crater with relative topography of ±70m has been discovered at the bottom of the basin (600-670m) 2)Western Kos basin with average depth of 520m. The basin is separated from the Eastern Kos Basin by a rise between Yali and Kos at 400m depth. This basin is separated from the Western Nisyros basin by the Kondeliousa rise. 3)The Western Nisyros basin is located between Kondeliousa rise and western Kos platform with depths of 550m. 4)The Southern Nisyros basin constitutes the northern end of the large Karpathos basin which reaches more than 2000m depth towards the south. 5)The Tilos basin with depths of 600m occurs southeast of Nisyros Island, separated from South Nisyros Basin through a rise of less than 400m depth. The Pachia-Pergoussa and Yali-Nisyros basins are shallow structures within the intra-volcanic relief of Nisyros and surrounding islets. The geometrty of each basin is discussed in relation to the volcanic and tectonic structure of the graben between Kos and Tilos.The intensity of the active geodynamic acrtivity is demonstrated by the creation of a volcanic relief of 1400m in the Nisyros volcanic field.